Hakikat Pencari Ilmu dalam Perspektif Pendidikan Islam: Integrasi Niat, Adab, Mujahadah, dan Tawakal dalam Proses Pembelajaran - Muhamad Thoif; Hasruddsin Dute; Mirza A`yunil Laili; Ahmad Buchori; Anco Anco (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to examine the essence of the seeker of knowledge (ṭālib al-‘ilm) from the perspective of Islamic education through the integration of four main concepts: intention (niyyah), ethics (adab), perseverance (mujahadah), and trust in God (tawakal). The study is motivated by the tendency of modern education to emphasize cognitive achievement and academic performance while often neglecting the spiritual, moral, and character-building dimensions of learners. This condition contributes to various moral issues and character crises among students. The research employs a qualitative approach using a library research method. Data were collected from primary sources, including the Qur’an, Hadith, and classical Islamic educational works such as Ta’lim al-Muta’allim and Ihya’ Ulumuddin, supported by relevant books and scholarly journals as secondary sources. Data analysis was conducted through content analysis involving data reduction, categorization, interpretation, and synthesis. The findings reveal that a seeker of knowledge in Islam is an individual who undergoes a holistic process of self-development. Intention serves as the spiritual foundation that directs learning objectives, ethics functions as a moral guideline, perseverance reflects dedication in the pursuit of knowledge, and trust in God represents reliance upon Allah after exerting maximum effort. The integration of these four values is highly relevant to modern education in fostering intellectually competent, morally upright, and spiritually resilient generations.